11(y-6)+5(y-7)=

Simple and best practice solution for 11(y-6)+5(y-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(y-6)+5(y-7)= equation:


Simplifying
11(y + -6) + 5(y + -7) = 0

Reorder the terms:
11(-6 + y) + 5(y + -7) = 0
(-6 * 11 + y * 11) + 5(y + -7) = 0
(-66 + 11y) + 5(y + -7) = 0

Reorder the terms:
-66 + 11y + 5(-7 + y) = 0
-66 + 11y + (-7 * 5 + y * 5) = 0
-66 + 11y + (-35 + 5y) = 0

Reorder the terms:
-66 + -35 + 11y + 5y = 0

Combine like terms: -66 + -35 = -101
-101 + 11y + 5y = 0

Combine like terms: 11y + 5y = 16y
-101 + 16y = 0

Solving
-101 + 16y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '101' to each side of the equation.
-101 + 101 + 16y = 0 + 101

Combine like terms: -101 + 101 = 0
0 + 16y = 0 + 101
16y = 0 + 101

Combine like terms: 0 + 101 = 101
16y = 101

Divide each side by '16'.
y = 6.3125

Simplifying
y = 6.3125

See similar equations:

| Ln(3x-1)=1.6 | | 10x=22783 | | Y+5x=23 | | Zy-3=10 | | 6-3(6+2x)=0 | | 0=-16t^2+245 | | 7(y-8)=9y-56 | | 10+5(2-2x)=0 | | h=245+16x^2 | | 245=-16t^2+h | | y=(2y)+15 | | 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 |

Equations solver categories